Chemical Regeneration of A Dye-Laden Activated Carbon: Optimization via The Box-Behnken Experimental Design - Enebi Estella Jasper; Jude Chinedu Onwuka; Edith Bolanle Agbaji (Pandawa Institute, 2023)
Activated carbon is widely used as an adsorbent to remove numerous pollutants from water and wastewater. The cost-effectiveness of an adsorbent depends upon its ability to be reused. This study focuses on regenerating Millettia thonningii seed pods' activated carbon (MAC) saturated with Methylene Blue (MB) using acetic acid as a regenerating solvent and exploring its potential to be reused. The effects of the variables such as, the concentration of the regenerating solvent, contact time, and volume of regenerating solvent on the regeneration process were ascertained using the Box-Behnken experimental design, which is a sub-set of Response Surface Methodology. The regeneration process was evaluated based on the desorption capacity of the active carbon. Scanning Electron Microscopy (SEM) and Fourier Transform Infrared spectroscopy (FTIR) was used to characterize the surface of the saturated active carbon before and after regeneration. Results revealed that the concentration of the regenerating solvent had the most significant synergistic effect on the regeneration process. The optimum conditions for the maximum regeneration of the spent activated carbon within the range of the variables studied were found to be: 8M acetic acid, 100 min, and 40 mL of acetic acid. The regenerated and pristine MAC when reused to adsorb fresh MB solutions (50 ml of 10mg/L MB: 0.2g adsorbent) had an adsorption capacity of 2.1912mg/g and 2.0977mg/g for MB respectively. Hence, the regenerated carbon outperformed the pristine active carbon. It could therefore be explored further as a recyclable adsorbent for wastewater treatment.